Analisis Kadar Kolesterol Low Density Lipoproteinsebagai Faktor Risiko Komplikasi pada Pasien Diabetes Melitus Tipe 2 - Pranita Aritrina; Asnah Marzuki; Fitriani Mangarengi (Halu Oleo University, 2016)
Dyslipidemia in type 2 diabetes mellitus (T2DM) can be increased the cardiovascular risk and this condition was equivalent with the elevated of LDL-cholesterol. In type 2 diabetes, LDL was small, dense and more aterogenic. This research was an observational study used cross sectional approach. The samples were 50 samples consist of twenty five of T2DM with non-CHD patient (50%) and twenty five of T2DM with CHD patient (50%) with age 45 years old or more. The level of serum LDL was measured by photometry used ABX Pentra 400. The data was analyzed by statistical method. The result study was conducted that normal LDL level was 9 (18%) patients and abnormal LDL level was 16 (32%) in T2DM with non-CHD patient. While in patient with T2DM with CHD had abnormal LDL level overall (50%). The high level of LDL in T2DM was accelerated complication occurrence, mainly coronary heart disease (CHD).Keywords: Type 2 diabetes mellitus (T2DM), dyslipidemia, LDL level, CHD complication